1980
DOI: 10.1104/pp.65.5.973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anoxia on ATP Levels and Ion Transport Rates in Red Beet

Abstract: in closed 25-ml flasks containing 5-7 ml experimental solution at 30 C. Peristaltic pumps were used to empty and refill the flasks at intervals without exposure to air. N2 treatments were applied by passing 02-free N2 gas into the flasks and at the same time replacing the solutions with solutions equilibrated with N2. For measurements of ATP content under N2, liquid N2 was poured into the flasks to freeze the tissue before exposing it to air. The frozen tissue was then extracted as described previously (2). RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Cellular ATP levels have been correlated with the rates of ion uptake (28), and recent studies with isolated membrane vesicles have demonstrated ATP-dependent, electrogenic proton transport (2,19). Similarities between the kinetics of K+ stimulation of ATPase and K+ uptake 6926 Botany: Briskin and Leonard into roots (18) and an analysis of K+ uptake data with respect to membrane potential (29) are consistent with a direct role for this enzyme in driving K+ transport.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular ATP levels have been correlated with the rates of ion uptake (28), and recent studies with isolated membrane vesicles have demonstrated ATP-dependent, electrogenic proton transport (2,19). Similarities between the kinetics of K+ stimulation of ATPase and K+ uptake 6926 Botany: Briskin and Leonard into roots (18) and an analysis of K+ uptake data with respect to membrane potential (29) are consistent with a direct role for this enzyme in driving K+ transport.…”
Section: Methodsmentioning
confidence: 99%
“…Beetroot cells are sensitive to anoxia and dependent on mitochondrial respiration for their energy needs ( Petraglia and Poole, 1980 ). The anoxia caused by flooding inhibits growth and produces PCD ( Chen et al, 2014 ; Kamal and Komatsu, 2015 ; Qi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since Beta vulgaris roots are reported to be sensitive to hypoxia ( Petraglia and Poole, 1980 ), it is conceivable that flooding could be an easy and adequate method to induce PCD in bulky roots similar to them. Then, after observing changes in the cell and nuclear morphology associated with cell death and the leakage of cyt c from mitochondria in flood-treated beetroots, it was concluded that flood stress could cause PCD in them.…”
Section: Introductionmentioning
confidence: 99%